Literature Survey Regarding with the Affects of Metro Lines On House Prices - Demircan, Kamil; Oguztimur, Senay (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
Metro lines are the most important part of urban rail systems. The socio-economic effects in this frame become an area of interest day by day, whereas studies regarding the effect of metro lines on increase of real estate prices prevail. However, there are also other studies and evaluations with different approaches. In this article, the studies regarding the effect of metro lines on real estate prices will be evaluated in terms of methods and findings, and various views around the world about these issues will be put forward. In this context, the purpose of this study is to summarize the different perspectives in the academic researches on how the metro lines affect the housing prices. According to the literature reviewed, metro lines have generally increased housing prices due to the increase in accessibility and positive externalities.
Keywords: Land price; hedonic price modelling; value capture; metro lines; railway lines; URBAN RAIL TRANSIT; LIGHT RAIL; LAND-VALUE; IMPACTS; Architecture